Tallinn manual on the international law applicable to cyber warfare : prepared by the international group of experts at the invitation of the NATO Cooperative Cyber Defence Centre of Excellence / general editor, Michael N. Schmitt. - Schmitt, Michael N. (Cambridge University Press, 2013)
The product of a three-year project by twenty renowned international law scholars and practitioners, the Tallinn Manual identifies the international law applicable to cyber warfare and sets out ninety-five 'black-letter rules' governing such conflicts. It addresses topics including sovereignty, State responsibility, the jus ad bellum, international humanitarian law, and the law of neutrality. An extensive commentary accompanies each rule, which sets forth the rule's basis in treaty and customary law, explains how the group of experts interpreted applicable norms in the cyber context, and outlines any disagreements within the group as to each rule's application.